Update on the Financing of PRGF and HIPC Operations and the Subsidization of Post-Conflict Emergency Assistance. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2002)
NULL.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: PP; PRGF Lending; PRGF Trust; Reserve Account; SDR; Burkina Faso